2005
DOI: 10.1159/000084336
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Canalith Repositioning for Anterior Semicircular Canal Canalithiasis

Abstract: The purpose of this study was to evaluate the efficacy of our canalith repositioning procedure (CRP) for benign paroxysmal positional vertigo (BPPV) of the anterior semicircular canal (ASC). We conducted a prospective study of 30 ASC BPPV patients to analyze the efficacy of a modified CRP. When the patient was diagnosed as having ASC BPPV by a specific provocative positioning test, a CRP was performed. The response to the treatment was categorized as grade I–IV. Of the 30 study patients, 6 were male and 24 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 19 publications
0
64
0
2
Order By: Relevance
“…The results from the current study indicated that the DH maneuver was successful in clearing ASC BPPV. The purpose of the DH maneuver was to remove physically the otoconia from the SCC and relocate them back into the utricle using gravity and a systematic progression of head position changes 4,10) . Approximately 95% of patients were clear within one or two treatments, and less than 5% of the patients required a third treatment session.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from the current study indicated that the DH maneuver was successful in clearing ASC BPPV. The purpose of the DH maneuver was to remove physically the otoconia from the SCC and relocate them back into the utricle using gravity and a systematic progression of head position changes 4,10) . Approximately 95% of patients were clear within one or two treatments, and less than 5% of the patients required a third treatment session.…”
Section: Discussionmentioning
confidence: 99%
“…Yacovino et al (2009) reported that all cases showed excellent therapeutic response to the DH maneuver 13) . Kim et al (2005) reported that vertigo and nystagmus in 29 patients were fully resolved using this maneuver and that 96.7% of patients became symptom free 10) . Based on these findings and our results, the DH maneuver could be one of the most effective treatment methods for ASC BPPV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Модифицированный репозиционный маневр при ДППГ ППК заключается в следующем: пациент усажива-ется на кушетку, его голова поворачивается на 45° в непо-раженную сторону [25]. Далее он укладывается на спину, не изменяя разворот головы, но глубоко запрокидывая ее назад на 30° (по возможности на 45°) ниже горизонталь-ной плоскости и удерживается в этом положении 2 мин.…”
Section: лечение дппг переднего полукружного канала (ппк)unclassified